Cell-type-specific brain methylomes profiled via ultralow-input microfluidics. (March 2018) - Ma, Sai; Fuente Revenga, Mario; Sun, Zhixiong; Sun, Chen; Murphy, Travis; Xie, Hehuang; González-Maeso, Javier; Lu, Chang
Abstract Methylomic analyses typically require substantial amounts of DNA, thus hindering studies involving scarce samples. Here, we show that microfluidic diffusion-based reduced representation bisulfite sequencing (MID-RRBS) permits high-quality methylomic profiling with nanogram-to-single-cell quantities of starting DNA. We used the microfluidic device, which allows for efficient bisulfite conversion with high DNA recovery, to analyse genome-wide DNA methylation in cell nuclei isolated from mouse brains and sorted into NeuN+ (primarily neuronal) and NeuN− (primarily glial) fractions, and to establish cell-type-specific methylomes. Genome-wide methylation and methylation in low-CpG-density promoter regions showed distinct patterns for NeuN+ and NeuN− fractions from the mouse cerebellum. The identification of substantial variations in the methylomic landscapes of the NeuN+ fraction of the frontal cortex of mice chronically treated with an atypical antipsychotic drug suggests that this technology can be broadly used for cell-type-specific drug profiling and for the study of drug–methylome interactions. A microfluidics-based sequencing method that profiles genome-wide DNA methylation using only sub-nanogram quantities of DNA finds distinct DNA methylome patterns in glial and neuronal cell nuclei from mouse brains treated with an antipsychotic drug.